(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
To comprehend the realistic paleo-bioclimate and depositional environment, we need to clearly grasp the methods that can be used to track paleoclimate in the past. The present research has focused on palynological investigation, X-ray Diffraction analysis, and elemental analysis of the core coal samples of the Gondwana coal of the Barapukuria Basin. The palynological study identifies two Palynoassemblage zones (Zone I and Zone II). A non-striate desiccate Scheuringipollenite, Crucisaccites, Parasaccites palynoassemblages are identified as Zone I and denotes as Lower Barakar Palynozone in the Early Permian where Zone II is dominated by striate desiccate Barakarites, Faunipollenites, Callumispora Palynoassemblages in the Late Permian. The Glossopterid plant family ruled the botanical affinity of Zone I and Zone II. It rendered the Gymnosperm group of plants as the rapid deglaciation assisted dissemination of Glossopteris flora. Higher percentages of clay minerals in X-ray diffraction (XRD) analysis and higher amounts of carbon content, lower sulfur, and higher C/S>10 ratio in the elemental analysis have been identified. All evidence from the research suggests that coals were deposited when glaciers retreated in the Early Permian, and the Gymnosperm group of plants prevailed and accumulated in the warm and humid climatic conditions under the braided fluvial influence in the terrestrial environment. J. Asiat. Soc. Bangladesh, Sci. 49(1): 101-119, June 2023